Biological Redox Impact of Tocopherol Isomers Is Mediated by Fast Cytosolic Calcium Increases in Living Caco-2 Cells - Miltha Hidalgo; Vania Rodríguez; Christine Kreindl; Omar Porras (MDPI AG, 2020)
Most of the biological impacts of Vitamin E, including the redox effects, have been raised from studies with α-tocopherol only, despite the fact that tocopherol-containing foods carry mixed tocopherol isomers. Here, we investigated the cellular mechanisms involved in the immediate antioxidant responses evoked by α-, γ- and δ-tocopherol in Caco-2 cells. In order to track the cytosolic redox impact, we performed imaging on cells expressing HyPer, a fluorescent redox biosensor, while cytosolic calcium fluctuations were monitored by means of Fura-2 dye and imaging. With this approach, we could observe fast cellular responses evoked by the addition of α-, γ- and δ-tocopherol at concentrations as low as 2.5 μM. Each isomer induced rapid and consistent increases in cytosolic calcium with fast kinetics, which were affected by chelation of extracellular Ca2+, suggesting that tocopherols promoted a calcium entry upon the contact with the plasma membrane. In terms of redox effects, δ-tocopherol was the only isomer that evoked a significant change in the HyPer signal at 5 μM. By mimicking Ca2+ entry with ionomycin and monensin, a decline in the HyPer signal was induced as well. Finally, by silencing calcium with 1,2-bis(o-aminophenoxy)ethane-N,N,N′,N′-tetraacetic acid (BAPTA), an intracellular Ca2+ chelator, none of the isomers were able to induce redox changes. Altogether, our data indicate that an elevation in cytoplasmic Ca2+ is necessary for the development of a tocopherol-induced antioxidant impact on the cytoplasm of Caco-2 cells reported by HyPer biosensor.